STUDI PENGELOLAAN ZAKAT PRODUKTIF PADA LEMBAGA AMIL ZAKAT NAHDLATUL ULAMA KABUPATEN LAMONGAN - Moh. Ah. Subhan ZA; Akmalur Rijal (Akademika, 2021)
The purpose of zakat to develop the social economic value of society is difficult to materialize if there is no active role of zakat managers (amil) who are required to be professional and innovative in managing zakat funds. The main function of the amil zakat institution lies in the activities of collecting, distributing, and utilizing zakat. The activity of collecting zakat in the history of Islam, is an activity or effort of amil in collecting zakat by picking up or taking from the place of amil. In addition to taking zakat, the amils who are in charge of taking zakat must also pray for those who pay zakat.This study aims to determine the implementation of productive zakat fund management and empowerment of the poor on zakat funds that are given by LAIZSNU Lamongan. By using the case study method, so as to be able to photograph how LAZISNU Lamongan's performance is in managing productive zakat funds . Lazisnu Lamongan has 3 zakat distribution programs, namely humanitarian, health and economic assistance. The mustahik empowerment program is included in the economic assistance program.